562 Biopsy of Localised Renal Masses Offers High Diagnostic Yield and Low Complication Rate in Patients with Suspicious Renal Masses. (12th October 2021) - Ng Cheong Chung, J; Isgro, G; Page, T; Thomas, D; Haslam, P; McNeil, A; Soomro, N; Rix, D; Rai, B; Veeratterapillay, R
Abstract: Aim: Biopsy of localised renal masses is generally accurate at detecting benign or malignant histology but can cause complications. The aim of this study was to determine the detection rate and complication rate of renal mass biopsies. Method: Patients undergoing a renal mass biopsy at a single tertiary centre between January 2015 and December 2019 were identified electronically using a prospective database. Details about their biopsies were recorded including tumour size, radiological guidance, number of cores, longest margin of biopsy, accuracy of biopsy, histology type, and complications. Results: This study included 334 biopsies (Median age 68 years (IQR 60-72); 61.4% (n = 204) male). Median size of tumour was 30mm (IQR 25-50) and 79.9% (n = 267) were solid masses. The biopsies were done under ultrasound (78.4%) or computed tomography (21.6%) guidance. 91.9% had core biopsies (n = 307) with median biopsy margin of 14mm (IQR 9-21). Benign histology was observed in 18.9% (n = 63), malignant in 72.1% (n = 241) while biopsy was non-diagnostic in 9.0% (n = 30). 62.6% (n = 209) of the cases were renal cell carcinoma with clear cell subtype more commonly seen (72.2%, n = 151). Complications following biopsy included haematoma (n = 7, 2.1%), haemorrhage (n = 3, 0.9%), pneumothorax (n = 1, 0.3%) and vasovagal episode (n = 1, 0.3%), resulting in an overall complication rate of 3.6%. Conclusions: Biopsy of localised renal masses in this study showed a detection rate of 91% and complication rate of 3.6%. This study suggests renal mass biopsies have high diagnostic yield and low complication rate.